Il ruolo politico delle imprese economiche: varietà di attori e modelli di mercato nell’azione pubblica - d’Albergo, Ernesto (SocietàMutamentoPolitica, 2017)
The article focuses on the emerging ways in which economic actors influence politics and policy. After an analysis of actions based on financial, relational and administrative resources, the article focuses on how the firms use knowledge and discourses in order to shape policy makers’ frames and beliefs. The final section presents provisional evidence about the political role of an Italian consulting firm.